PO002 Bacterial meningitis with myelopathy and cranial neuropathy. (1st December 2017) - Ahrabian, Dariush; Blundell, Samkeliso; Chinthapalli, Krishna; Cummins, Gemma; Howard, Robin; Wild, Edward J
Abstract : Acute meningococcal meningitis in adults can be complicated by cranial neuropathies and more rarely by myelopathy. A 55-year-old woman presented with acute bacterial meningitis requiring intubation and was treated with intravenous antibiotics and dexamethasone. Cerebrospinal fluid 16S PCR was positive for Neisseria meningitidis and latex agglutination confirmed the W135 serotype. Ten days after presentation she developed mild upper limb and severe lower limb weakness with hyperreflexia, despite resolution of meningism and improvement of inflammatory markers. On the next day she developed complete bilateral hearing loss and bilateral facial palsy. Magnetic resonance imaging with contrast showed bilateral enhancement of VIIth and VIIIth cranial nerves, with focal signal change within the thoracic spinal cord. Audiometry confirmed complete sensorineural deafness. She was treated with five days of intravenous methylprednisolone and continued a further nine days of intravenous antibiotics. Four weeks after onset, she remained completely deaf with mild improvement of limb and facial weakness. We report a case of acute meningococcal meningitis complicated by presumed extensive vasculitis leading to myelopathy and delayed onset of multiple cranial neuropathies. There was an unusual biphasic presentation and the vasculitis was apparently ameliorated by glucocorticoids, suggesting conventional steroid recommendations may occasionally be inadequate.